Impact of Tiktok Live Stream Attributes on Social Presence and Behavioral Intention Among Surabaya Users - Made Nibbana Ganesha Putra Artha; Timotius FCW Sutrisno (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: The use of live streaming on a social commerce platform is now an innovative step for business actors in marketing their products in real-time that can reach a wider market through digitalization. Purpose: The purpose of this study is to analyze the effect of livestream attributes on social presence and behavioral intention also aims to determine the effect of motivational mindset as a moderator.Design/Methodology/Approach: This research uses a quantitative method by distributing questionnaires online using a purposive sampling method to 200 sample respondents who have used and made transactions via live streaming TikTok Shop in Surabaya. The analysis technique used in this research is descriptive statistical analysis using the SEM-PLS and the data is processed using Smart PLS. Findings/Result: The results of the study stated that sociability has a positive significant effect on social presence, while information task fit and visual effect do not have a significant effect on social presence. Social presence has a significant effect on behavioral intention. Promotion focus does not moderate while prevention focus moderates the effect of social presence on the behavioral intention. Conclusion: Broadcasters need to focus on sociability such as friendliness to create a social presence for potential customers to make purchases.Originality/value (State of the art): The difference is the social commerce used, namely TikTok Shop, and previous studies using QQ and WeChat. This also complements previous research that suggests testing in each country with different societies, such as economic levels, political backgrounds, and cultural backgrounds, especially in Surabaya, Indonesia. Keywords: live stream attributes; social presence; behavioral intention; online live streaming shopping; motivational mindset